Perbandingan model pembelajaran kooperatif tipe Course Review Horray dan STAD terhadap peningkatan pemahaman matematis siswa - Bettri Yustinaningrum; Leni Agustina Daulay; Dina Yulisa Putri (STKIP PGRI Banjarmasin, 2019)
The purpose of this study was to (1) compare the Course Review Horay (CRH) learning model with STAD in improving students' mathematical understanding, (2) describe the increase in mathematical understanding of students using CRH and STAD, (3) find out the feasibility of the Course Review Horay learning model (CRH) with STAD through activities of observing teacher and student activities. The form of this research is quantitative research with semi-experimental research types. The research sample was selected by Cluster Random Sampling obtained by two classes of students X Science 2 and X IPA 3 Takengon N 15 High School. Data collection techniques used are tests and observations. Hypothesis testing uses a 1-party t-test and an increase using the N-gain test. The results obtained by tcount> t table where 2.44> 2.01, with a significant level of 0.05 and dk = 26 + 26 - 2 = 50, thus H0 is rejected and Ha is accepted. The increase in the ability of mathematical understanding using the CRH learning model is more significant at g = 0.66 compared to STAD at g = 0.33. Based on the results of this study it can be concluded that the Course Review Horay (CRH) learning model is better than STAD in improving students' mathematical understanding.